Multilingualism and Translanguaging in Chinese Language Classrooms - Wang, Danping (Palgrave Studies in Teaching and Learning Chinese, 2019)
'A timely addition to the growing literature on teaching Chinese as an international language and a valuable contribution to language education research.' -Li Wei, Chair of Applied Linguistics, University College London, UK This book presents new research on Chinese as a Second Language (CSL) teaching from an ethnographic classroom study on classroom translanguaging practices that highlights the policy and pedagogical implications of adopting a creative and principled multilingual approach. Drawing on a case study from Hong Kong, it analyses naturally observed language patterns in CSL classrooms and the attitudes of students and teachers towards prescribed classroom language policies, and thereby demonstrates the importance of mixing Chinese, English and students' home languages to achieve successful second language learning. It discusses the nature and guiding principles for classroom translanguaging research and provides research tools that will enable second language teachers to examine their own language practices. The author argues persuasively that second language teaching practices and policies must reflect the current reality of language use and the diverse learning needs of multilingual students. This book will appeal to teacher educators and researchers in fields such as second language acquisition, foreign language teaching and language policy. Danping Wang is a lecturer in Chinese in the School of Cultures, Languages and Linguistics, University of Auckland, New Zealand. She was awarded Teaching Excellence Award and Sino-British Fellowship for her active and innovative contributions in Chinese language education.